Minerals, antinutrients content and the bioaccessibility of iron and zinc in cooked, spontaneously fermented-dried, and blanched-dried dark green leafy vegetables commonly consumed in Sub-Saharan Africa - MONGWAKETSE,Tiyapo (2022)
Abstract Iron and zinc deficiencies remain a significant problem in sub-Saharan Africa. This study aimed at determining mineral, antinutrient contents of differently processed ALVs, and the bioaccessibility of iron and zinc from cooked, blanched-dried, as well as spontaneously fermented-dried ALVs. Mineral and antinutrient contents of ALVs were analysed and the bioaccessibility of iron and zinc from ALVs were analysed by in vitro dialysability assay. Iron, zinc, magnesium, and calcium contents of the ALVs were high. Compared to cooked vegetables, both spontaneously fermented-dried and blanched-dried vegetables had significantly lower levels of condensed tannins, while significantly lower total phenolic contents were found in blanched-dried vegetables. Compared to cooked counterparts, percentage iron and zinc bioaccessibilities in spontaneously fermented-dried and blanched-dried ALVs showed no significant (p > 0.05) differences except for iron in Ethiopian kale and zinc in amaranth. Based on data from this study, it is recommended that ALVS should be consumed concurrently with iron and zinc enhancers to enhance bioaccessibility.